Analysis of weekly rainfall for crop planning in Udaipur region - Jat, M L; Singh, R V; Balyan, J K; Jain, L K (Journal of Agricultural Engineering, 2005)
Probability analysis of rainfall offers a better scope for predicting the minimum assured rainfall to help in crop planning in rainfed regions. Incomplete gamma distribution is used to predict the minimum assured rainfall at different probability of excedence in all weeks of the whole year The study reveals that chances of drought are more at critical stages of maize and there is a scope for in-situ moisture conservation and runoff collection in tanks for supplemental irrigation. Rabi crops are found to be grow under moisture stress.